Polyvinyl chloride composite, polyvinyl chloride toughening and reinforcing master batch and preparation method thereof

CN117511088BActive Publication Date: 2026-10-23HUBEI WANJIN TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311550988.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2026-10-23
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

[0007]但是,双轴取向改性的生产工艺,仍受制于PVC材料本身的特性,使抗冲击性提高有限;相容性高分子材料的共混虽然能提高韧性,但是会牺牲PVC的强度、模量及热稳定性;刚性粒子、短纤维及其他维度材料的添加,能改善韧性和强度,但是由于界面粘结问题,使性能的改善并不显著,而且会牺牲PVC的低温性能

Benefits of technology

[0023]该聚氯乙烯复合材料具有如下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a polyvinyl chloride composite material, a polyvinyl chloride toughening and reinforcing master batch and a preparation method thereof, and belongs to the technical field of polyvinyl chloride modification. The raw material composition of the polyvinyl chloride composite material comprises, in mass percentage, 0.2-20% of hyperbranched polyurethane grafted carbon nanotubes, 0.2-20% of hyperbranched polyurethane grafted graphene nanosheets, 0.2-20% of nano silicon dioxide, 0.1-1% of an antioxidant, 2-5% of a heat stabilizer and the balance of polyvinyl chloride. The application is aimed at the brittleness problem of polyvinyl chloride pipes, and hyperbranched polyurethane modified reinforcing bodies (carbon nanotubes and graphene nanosheets) and nano silicon dioxide are filled into the PVC. On the one hand, the reinforcing bodies with different dimensions are used to improve the mechanical strength of the PVC; on the other hand, the spherical structure of the hyperbranched polyurethane is used to improve the interface structure of the reinforcing bodies and the PVC, and the impact resistance of the PVC is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyvinyl chloride modification technology, and specifically relates to a polyvinyl chloride composite material, a polyvinyl chloride toughening and reinforcing masterbatch, and a method for preparing the same. Background Technology

[0002] PVC pipes are widely used in construction, water supply, drainage, power, and telecommunications, ranking first in global sales volume. With increasing market demand, the application range of PVC pipes is becoming increasingly broad. However, during production and use, the inherent brittleness of PVC material makes it difficult to withstand external impacts, leading to problems such as cracking and breakage, especially in low-temperature environments. This limitation restricts the widespread application of PVC.

[0003] Currently, the scientific and industrial communities have developed a series of measures to improve the impact resistance of PVC. In production, a biaxial orientation modification process is adopted, which controls the orderly arrangement of PVC molecular chains during processing to achieve a toughening effect. This greatly enhances the mechanical strength and impact toughness of the pipes. Under the same pressure, it can also significantly reduce the wall thickness and weight of the pipes, thus saving resources and reducing product costs.

[0004] From the perspective of material modification, by changing the composition and microstructure of PVC, the impact resistance of PVC pipes is also improved. ① Add polyurethane, SBS, NBR and other elastomer impact modifiers to PVC and blend them together. Utilize the toughness of these impact modifiers themselves and their good compatibility with PVC to improve the toughness of PVC and thus enhance its impact resistance.

[0005] ② By connecting flexible molecular chain segments to the PVC molecular chain through copolymerization, grafting, crosslinking and other methods, the molecular chain structure of PVC is controlled, its toughness and strength are improved, and it has good durability in low temperature environment.

[0006] ③ Adding organic rigid particles (PMMA, PS, etc.), inorganic rigid particles (nano CaCO3, nano SiO2, ultrafine kaolin, etc.), short-cut fibers (glass fiber, carbon fiber), graphene sheets, carbon nanotubes, etc., as reinforcing agents to PVC can not only significantly improve the impact toughness of PVC, but also improve the tensile strength, heat distortion temperature, processing fluidity and other properties of PVC.

[0007] However, the biaxial orientation modification process is still limited by the characteristics of PVC material itself, which limits the improvement of impact resistance; although blending with compatible polymer materials can improve toughness, it will sacrifice the strength, modulus and thermal stability of PVC; the addition of rigid particles, short fibers and other dimensional materials can improve toughness and strength, but due to interfacial bonding problems, the performance improvement is not significant and the low-temperature performance of PVC will be sacrificed.

[0008] Therefore, how to effectively improve the impact resistance of PVC pipes while taking into account their strength and thermal stability, so that they have better mechanical properties in complex environments, is a key technical problem that needs to be solved. Summary of the Invention

[0009] This invention addresses the brittleness problem of polyvinyl chloride (PVC) pipes by filling PVC with hyperbranched polyurethane-modified reinforcements (carbon nanotubes, graphene nanosheets) and nano-silica. On one hand, the reinforcements with different dimensional gradations improve the mechanical strength of PVC; on the other hand, the spherical structure of the hyperbranched polyurethane improves the interface structure between the reinforcements and PVC, thereby enhancing the impact resistance of PVC. The technical solution provided by this invention is as follows: On one hand, embodiments of the present invention provide a polyvinyl chloride composite material, the raw material composition of which includes, by mass percentage: Hyperbranched polyurethane-grafted carbon nanotubes: 0.2-20%; Hyperbranched polyurethane-grafted graphene nanosheets: 0.2-20%; Nano-silica 0.2-20%; Antioxidant 0.1-1%; Heat stabilizer 2-5%; Polyvinyl chloride balance.

[0010] Among them, the degree of polymerization of polyvinyl chloride is 1700-2500; the particle size of nano-silica is 10-500nm, and it is a spherical particle; the carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes; the weight average molecular weight of hyperbranched polyurethane is 3000-100000, the thickness of the hyperbranched polyurethane coating layer on the surface of carbon nanotubes is 5-80nm, and the thickness of the hyperbranched polyurethane coating layer on the surface of graphene nanosheets is 5-80nm.

[0011] Among them, hyperbranched polyurethane-grafted carbon nanotubes, hyperbranched polyurethane-grafted graphene nanosheets, and nano-silica are all reinforcements. Both hyperbranched polyurethane-grafted carbon nanotubes and hyperbranched polyurethane-grafted graphene nanosheets are modified by hyperbranched polyurethane.

[0012] Preferably, the polyvinyl chloride composite material provided by the present invention comprises, by mass percentage: Hyperbranched polyurethane-grafted carbon nanotubes: 1-4%; Hyperbranched polyurethane-grafted graphene nanosheets, 2.5-6.0%; Nano-silica 1.0-3.5%; Antioxidant 0.1-0.3%; Heat stabilizer 3-5%; Polyvinyl chloride balance.

[0013] Preferably, the carbon nanotubes are single-walled carbon nanotubes.

[0014] Preferably, the hyperbranched polyurethane has a weight-average molecular weight of 3000-10000, and the coating thickness of the hyperbranched polyurethane on the carbon nanotube surface is 10-45 nm, as is the coating thickness of the hyperbranched polyurethane on the graphene nanosheet surface. Both the carbon nanotubes and graphene nanosheets are commercially available products; taking graphene nanosheets as an example, their dimensions are: length 1-15 μm, width 1-15 μm, and thickness 5-30 nm. Specifically, the graphene nanosheets can be graphene prepared by CVD or reduced graphene oxide prepared by wet processing.

[0015] More preferably, the polyvinyl chloride composite material provided by the present invention comprises, by mass percentage: Hyperbranched polyurethane-grafted single-walled carbon nanotubes: 2.5%; Hyperbranched polyurethane-grafted graphene nanosheets 4.5%; Nano-silica 2.5%; Antioxidant 0.1%; Heat stabilizer 3.5%; Polyvinyl chloride balance.

[0016] Among them, the degree of polymerization of polyvinyl chloride is 1700-2500; the particle size of nano-silica is 20nm; the weight average molecular weight of hyperbranched polyurethane is 3000-10000; the coating thickness of hyperbranched polyurethane on the surface of carbon nanotubes is 20nm; and the coating thickness of hyperbranched polyurethane on the surface of graphene nanosheets is 20nm.

[0017] The hyperbranched polyurethane-grafted carbon nanotubes in this invention are obtained by treating carbon nanotubes with oxygen-containing plasma for 10-40 minutes to imbue the surface of the reinforcement with carboxylic acid groups, followed by reaction with hyperbranched polyurethane (whose molecular chain has a large number of hydroxyl groups). Similarly, the hyperbranched polyurethane-grafted graphene nanosheets are obtained by treating graphene nanosheets with oxygen-containing plasma for 10-40 minutes to imbue the surface of the reinforcement with carboxylic acid groups, followed by reaction with hyperbranched polyurethane (whose molecular chain has a large number of hydroxyl groups).

[0018] The antioxidants and heat stabilizers used in this invention are common additives for polyvinyl chloride (PVC). Specifically, the heat stabilizers in this invention are selected from one or more of organotin heat stabilizers and epoxy compound heat stabilizers, and the antioxidants are selected from one or more of phosphite antioxidants and hindered phenolic antioxidants.

[0019] On the other hand, embodiments of the present invention also provide a polyvinyl chloride toughening and reinforcing masterbatch, which is processed from the aforementioned polyvinyl chloride composite material.

[0020] In another aspect, embodiments of the present invention also provide a method for preparing a toughening and reinforcing masterbatch for polyvinyl chloride, the method comprising: (1) The carbon nanotubes grafted with hyperbranched polyurethane, the graphene nanosheets grafted with hyperbranched polyurethane, the nano-silica, the antioxidant, the heat stabilizer and polyvinyl chloride are mixed according to the ratio to obtain the polyvinyl chloride composite material.

[0021] (2) Polyvinyl chloride profile composite material is extruded and pelletized in a twin-screw extruder to obtain polyvinyl chloride toughening and reinforcing masterbatch.

[0022] Specifically, the extrusion conditions of the twin-screw extruder are as follows: Zone 1 temperature is 164-170℃, Zone 2 temperature is 168-175℃, Zone 3 temperature is 170-190℃, Zone 4 temperature is 175-190℃, screw speed is 30-45 rpm, and feed speed is 20-40 rpm.

[0023] This polyvinyl chloride composite material has the following advantages: (1) The ordered arrangement of graphene during the extrusion process is used to toughen the tube and improve its impact resistance. The high aspect ratio and effective distribution of one-dimensional nanotubes form a spatial network connected with graphene sheets, achieving both reinforcement and toughening. The close packing of zero-dimensional nano-SiO2 can solve the problem of low density and insignificant improvement in mechanical strength caused by the bridging effect of graphene sheets and carbon nanotubes in the matrix. Optimizing the ratio of the three dimensions of reinforcement and controlling the distribution of reinforcement in the matrix ensures the simultaneous improvement of the material's mechanical properties, impact resistance, and thermal stability.

[0024] (2) Hyperbranched polyurethane is used to graft and modify the nano-reinforcement, overcoming the problem that adding unmodified reinforcement and conventionally linearly modified reinforcement to the matrix weakens the processability of the matrix. On the one hand, hyperbranched polyurethane does not reduce the low-temperature performance of PVC; on the other hand, the spherical distribution of hyperbranched polyurethane on the surface of nanoparticles is beneficial to reducing the entanglement between the polymer chains of the reinforcement and the matrix during melt processing, reducing the melt viscosity of the matrix, and improving its processability. Optimizing the grafting ratio of hyperbranched polyurethane can control the interface and rheological properties of the composite material, ensuring the simultaneous improvement of the material's mechanical properties, impact resistance, thermal stability, and processability. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in further detail below.

[0026] Example 1: Example 1 provides a method for preparing a toughening and reinforcing masterbatch for polyvinyl chloride (PVC), comprising: treating single-walled carbon nanotubes and graphene nanosheets in an oxygen plasma atmosphere for 30 min, then melt-blending them with hyperbranched polyurethane, grafting the hyperbranched polyurethane onto the walls of the single-walled carbon nanotubes and onto the surface of the graphene nanosheets, controlling the amount added to achieve a coating layer thickness of approximately 40.6 nm. Then, 1.5% (by mass percentage, the same below) of grafted modified single-walled carbon nanotubes, 2.8% of grafted modified graphene nanosheets, and 1.5% of nano-silica with a particle size of approximately 20 nm are blended with PVC. Before melt processing, 0.1% of an antioxidant and 3.5% of a heat stabilizer are added. The above materials are mixed and added to a conical twin-screw extruder. The temperature of zone 1 is controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃, and zone 4 at 175℃. The screw speed is 35 rpm and the feeding speed is 25 rpm. The mixture is then melt-extruded and pelletized to obtain PVC toughening and reinforcing masterbatch.

[0027] Example 2: Example 2 provides a method for preparing a toughening and reinforcing masterbatch for polyvinyl chloride (PVC), comprising: treating single-walled carbon nanotubes and graphene nanosheets in an oxygen plasma atmosphere for 30 min, then melt-blending them with hyperbranched polyurethane, grafting the hyperbranched polyurethane onto the walls of the single-walled carbon nanotubes and onto the surface of the graphene nanosheets, controlling the amount added to achieve a coating layer thickness of 10.5 nm. Then, 3% grafted modified single-walled carbon nanotubes, 5.5% grafted modified graphene nanosheets, and 3.2% nano-silica with a particle size of approximately 20 nm are blended with PVC. Before melt processing, 0.1% antioxidant and 3.5% heat stabilizer are added. The polyvinyl chloride mixture was added to a conical twin-screw extruder, and under the conditions of controlling the temperature of zone 1 to 168℃, zone 2 to 175℃, zone 3 to 190℃, zone 4 to 190℃, screw speed to 40 rpm, and feeding speed to 30 rpm, it was melt-extruded and pelletized to obtain polyvinyl chloride toughening and reinforcing masterbatch.

[0028] Example 3: Example 3 provides a method for preparing a toughening and reinforcing masterbatch for polyvinyl chloride (PVC), comprising: treating single-walled carbon nanotubes and graphene nanosheets (prepared by reduction oxidation) in an oxygen plasma atmosphere for 15 min respectively, then melt-blending them with hyperbranched polyurethane, grafting the hyperbranched polyurethane onto the walls of the single-walled carbon nanotubes and onto the surface of the graphene nanosheets respectively, controlling the amount added to make the coating layer thickness about 20 nm. Then, 2.5% grafted modified single-walled carbon nanotubes, 4.5% grafted modified graphene nanosheets, and 2.5% nano-silica with a particle size of about 30 nm are blended together with PVC. Before melt processing, 0.1% antioxidant and 3.5% heat stabilizer are added. Then, the polyvinyl chloride mixture is added to a conical twin-screw extruder, and under the conditions of controlling the temperature of zone 1 to be 165℃, zone 2 to be 170℃, zone 3 to be 180℃, and zone 4 to be 178℃, the screw speed to be 40 rpm, and the feeding speed to be 30 rpm, it is melt-extruded and pelletized to obtain polyvinyl chloride toughening and reinforcing masterbatch.

[0029] Comparative Examples 1-7 were designed relative to Example 1, and the conditions not described were the same as in Example 1.

[0030] Comparative Example 1: PVC, 0.1% antioxidant and 3.5% heat stabilizer were added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃ and zone 4 at 175℃. The screw speed was 35 rpm and the feeding speed was 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0031] Comparative Example 2: PVC, 0.1% antioxidant, 3.5% heat stabilizer and 1.5% single-walled carbon nanotubes were added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃ and zone 4 at 175℃, the screw speed was 35 rpm and the feeding speed was 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0032] Comparative Example 3: PVC, 0.1% antioxidant, 3.5% heat stabilizer and 2.8% graphene nanosheets were mixed and added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃ and zone 4 at 175℃, the screw speed was 35 rpm and the feeding speed was 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0033] Comparative Example 4: PVC, 0.1% antioxidant, 3.5% heat stabilizer, 1.5% single-walled carbon nanotubes, 2.8% graphene nanosheets, and 1.5% nano-silica with a particle size of 20nm were added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃, and zone 4 at 175℃. The screw speed was 35 rpm and the feeding speed was 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0034] Comparative Example 5: PVC, 0.1% antioxidant, 3.5% heat stabilizer, 1.5% hyperbranched polyurethane-grafted single-walled carbon nanotubes, and 2.8% hyperbranched polyurethane-grafted graphene nanosheets were added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃, and zone 4 at 175℃. The screw speed was 35 rpm and the feeding speed was 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0035] Comparative Example 6: PVC, 0.1% antioxidant, 3.5% heat stabilizer and 1.5% hyperbranched polyurethane grafted single-walled carbon nanotubes were added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃, zone 4 at 175℃, screw speed at 35 rpm and feeding speed at 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0036] Comparative Example 7: PVC, 0.1% antioxidant, 3.5% heat stabilizer and 2.8% hyperbranched polyurethane-grafted graphene nanosheets were added to a conical twin-screw extruder. The temperature of zone 1 was controlled at 165℃, zone 2 at 170℃, zone 3 at 175℃, zone 4 at 175℃, screw speed at 35 rpm and feeding speed at 25 rpm. The mixture was then melt-extruded and pelletized to obtain polyvinyl chloride masterbatch.

[0037] The results are shown in Tables 1 and 2: Table 1. Hack rheological properties of different resin samples As can be seen from Table 1, compared with the comparative example, the composite material of this patent has similar processing conditions (similar mixing temperature and speed), lower balancing torque and shorter plasticizing time, resulting in better processing performance.

[0038] Table 2. Mechanical strength and impact resistance data of different resin samples As can be seen from Table 2, compared with the comparative example, the composite material of this patent has higher average tensile strength, room temperature notched impact strength and low temperature notched impact strength.

[0039] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A polyvinyl chloride composite material, characterized in that, Its raw material composition, by mass percentage, includes: Hyperbranched polyurethane-grafted single-walled carbon nanotubes: 2.5%; Hyperbranched polyurethane-grafted graphene nanosheets 4.5%; Nano-silica 2.5%; Antioxidant 0.1%; Heat stabilizer 3.5%; Polyvinyl chloride balance; Among them, the degree of polymerization of polyvinyl chloride is 1700-2500; the particle size of nano-silica is 20nm; the weight average molecular weight of hyperbranched polyurethane is 3000-10000; the coating thickness of hyperbranched polyurethane on the surface of single-walled carbon nanotubes is 20nm; and the coating thickness of hyperbranched polyurethane on the surface of graphene nanosheets is 20nm. Hyperbranched polyurethane-grafted single-walled carbon nanotubes: Single-walled carbon nanotubes were treated with oxygen-containing plasma for 10-40 min and then reacted with hyperbranched polyurethane; The source of hyperbranched polyurethane-grafted graphene nanosheets was: Graphene nanosheets were treated with oxygen-containing plasma for 10-40 min and then reacted with hyperbranched polyurethane. The heat stabilizer is selected from one or more of organotin heat stabilizers and epoxy compound heat stabilizers, and the antioxidant is selected from one or more of phosphite antioxidants and hindered phenolic antioxidants; The dimensions of the graphene nanosheets are: length 1-15μm, width 1-15μm, and thickness 5-30nm.

2. A toughening and reinforcing masterbatch for polyvinyl chloride, characterized in that, It is manufactured using the polyvinyl chloride composite material as described in claim 1.

3. The method for preparing the polyvinyl chloride toughening and reinforcing masterbatch as described in claim 2, characterized in that, The method includes: (1) Mix hyperbranched polyurethane-grafted single-walled carbon nanotubes, hyperbranched polyurethane-grafted graphene nanosheets, nano-silica, antioxidants, heat stabilizers and polyvinyl chloride according to the specified ratio to obtain polyvinyl chloride composite material. (2) Polyvinyl chloride profile composite material is extruded and pelletized in a twin-screw extruder to obtain polyvinyl chloride toughening and reinforcing masterbatch.

4. The preparation method according to claim 3, characterized in that, The extrusion conditions for the twin-screw extruder are as follows: Zone 1 temperature 164-170℃, Zone 2 temperature 168-175℃, Zone 3 temperature 170-190℃, Zone 4 temperature 175-190℃, screw speed 30-45 rpm, and feeding speed 20-40 rpm.

Citation Information

Patent Citations

  • Environmentally-friendly antistatic graphene-modified rigid PVC plastic used for plates and preparation method of PVC plastic

    CN108003494A

  • Cold-resistant polyvinyl chloride (PVC) sheet

    CN108503974A

  • Super-branched polymer grafted carbon nanotube and its prepn process

    CN1486927A